(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes methodological challenges in teaching damped mechanical oscillations and suggests possible solutions. It is noted that complex mathematical expressions and abstract concepts create difficulties for students. Therefore, the necessity of using digital technologies, virtual laboratories, and modeling tools is substantiated. The proposed methodological recommendations aim to integrate theory with practice and enhance students’ motivation.